(untitled) (Journal of history, 2024)
The article is determined by the growing interest in establishing the role and mission of the national intelligentsia in the criteria of socio-political transformation of society, which requires a deep understanding and modeling of national value orientations. The importance of the social and cultural phenomenon of the intelligentsia is determined by the specific nature of the activities and the results of the work of representatives of secular labor. In addition, the need to identify effective mechanisms of relations between the state and administrative apparatus with various groups of intellectuals and the need to address issues of the effectiveness of the functioning of regional branches of professional organizations at the present stage. In this way, the existing set of academic, political, social, and cultural-historical factors indicates the need to increase new scientific knowledge on the topic of research. The problems that consider the participation of the Kazakh intelligentsia in the cultural construction of the 20-30s of the twentieth century, and the associated difficulties of education, the creation of a new type of intelligentsia, were the focus of attention of the political leadership of the Kazakh SSR T. Ryskulov, F. Goloshchekin, G. Togzhanov, L. Mirzoyan, etc. Keywords: cultural modernization, Kazakhstan, Kazakh intelligentsia, Soviet literature, enlightenment.